(untitled) (The Pretoria Student Law Review, 2021)
This article serves as an analysis of the depiction of the neutrality and objectivity of judges through the image of Lady Justice. I will investigate whether this depiction is relevant under the current constitutional dispensation, bearing in mind a value-orientated approach to law. Firstly, I will discuss the historical development of the image of Lady Justice with regards to adjudication. Secondly, I will analyse the relevance of Lady Justice in a post-apartheid South African context. Thirdly, I will provide a discussion on the postapartheid contextual meaning of reconciliation and the onus of a value-orientated approach to adjudication that the Constitution has placed on the courts.